2017
DOI: 10.1101/235606
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sleep spindle refractoriness segregates periods of memory reactivation

Abstract: Abstract:The stability of long-term memories is enhanced by reactivation during sleep. Correlative evidence has linked memory reactivation with thalamocortical sleep spindles, although their functional role is poorly understood. Our initial study replicated this correlation but also demonstrated a novel rhythmicity to spindles, such that spindles are less likely to occur immediately following other spindles. We leveraged this rhythmicity to test the role of spindles in memory by using real-time spindle trackin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 34 publications
4
17
1
Order By: Relevance
“…We averaged RMS values across specified time windows for each subject and calculated differences across conditions using within-subject t-tests. Our specified precue window was Ϫ2000 to 0, based on a previous study (Antony et al, 2018b). Our a priori postcue window was 1000 to 1500 ms (Antony et al, 2018a), although we eventually widened this window to 1000 to 4500 ms after observing that left/right decoding accuracy stayed above chance up to 4.5 s after cue onset.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We averaged RMS values across specified time windows for each subject and calculated differences across conditions using within-subject t-tests. Our specified precue window was Ϫ2000 to 0, based on a previous study (Antony et al, 2018b). Our a priori postcue window was 1000 to 1500 ms (Antony et al, 2018a), although we eventually widened this window to 1000 to 4500 ms after observing that left/right decoding accuracy stayed above chance up to 4.5 s after cue onset.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we anticipated that postcue spindles would positively predict lateralized evidence of retrieval during sleep, as well as subsequent memory during the postnap test. Furthermore, prior work has shown that spindles have a refractory period of 3-6 s, during which TMR cues are less effective (Antony et al, 2018b); as such, we expected that precue spindles would negatively predict both lateralized evidence of retrieval and subsequent memory.…”
Section: Introductionmentioning
confidence: 92%
“…Accordingly, an intimate relationship between TMR and sleep spindles has been established. Promoting memory reactivation via TMR has been demonstrated to cause a robust surge in sleep spindle activity [120,[126][127][128][129][130]. In addition, a growing number of TMR studies also point towards a critical role of theta with regards to memory reactivation during sleep.…”
Section: (I) Identifying Memory Reactivation Using Multivariate Appromentioning
confidence: 99%
“…Interestingly, memory cueing during night is not restricted to the olfactory modality, as auditory cues, even the auditory presentation of previously learned words during SWS, also work 13,19,20 . However, continuous stimulation with auditory cues can be problematic because of a certain refractoriness pattern: Auditory stimulus presentation needs to be below a certain temporal duration 33 and spaced in time within the SWS stage in order to prevent the disappearance of the beneficial effect of cueing. The latter strongly reminds of well-known spacing effects 15,[34][35][36] or retroactive interference effects during learning 16 .…”
Section: Do Odor Cues During Sleep Improve Both Memory Consolidation mentioning
confidence: 99%